The Muslim Brothers in Pursuit of Legitimacy: Power and Political Islam in Egypt under Mubarak. - Al-Awadi, Hesham (2016)
Following the 25th January revolution, the Muslim Brotherhood emerged as the most organized and successful political force in Egypt, cashing in on decades of grassroots mobilization and growth. Through dominance in syndicates and unions, the provision of social services and participation in elections, the Brotherhood steadily expanded under Mubarak. Hesham Al-Awadi's lucid and original argument frames this period as one of struggle over legitimacy between the regime and this then outlawed movement. He charts a cycle of accommodation and coercion as the Brotherhood gained an informal social legitimacy, yet failed to secure regime recognition. Through the complex dynamics of conflict and control, Al-Awadi sheds light on the Mubarak era and the Muslim Brotherhood that have risen out of it.